Motivation for Compliance of People With HIV and AIDS in Taking Antiretrovirals (ARVs) in Kupang City 2019 - Lesik, Marlin Nurati; Manurung, Imelda F.E; Limbu, Ribka (Faculty of Public Health, Nusa Cendana University, 2020)
Efforts to reduce HIV and AIDS infection can be done by taking antiretroviral virus (ARV) drugs. Behavioral compliance in treatment is one way to maintain so that PLWHA (people with HIV and AIDS) can live longer. Factors supporting adherence to taking ARV medication are self-motivation including, attitude to recover, belief / belief in healing, support from family, and support of health workers. The purpose of this study is to find out how motivation for adherence of people with HIV / AIDS in consuming Antiretroviral (ARV) in Kupang City in 2019. The type of research used in this study is descriptive qualitative. This research informants numbered 5 people. This study uses in-depth interview techniques (Indepth Interview). Data analysis was performed with qualitative analysis based on data obtained through unstructured interviews with informants. The results of the study found that PLWHA have the motivation to adhere to taking antiretrovirals. Although there are still PLWHA who are late taking medication and dropping out due to antiretroviral side effects. In addition, there is a belief from PLWHA about the benefits of ARV therapy to make PLWHA healthy again, having hopes of a drug that can cure AIDS. The family's acceptance of the AIDS status suffered by PLWHA and supporting PLWHA to take ARV drugs and the support of health workers are supporting factors that motivate PLWHA to comply with antiretroviral consumption. From the results of the study it is expected that all PLWHA will always take ARV medicines on time and regularly check their health at a health facility.